Dynamic tests of CO2-Based waste heat recovery system with preheating process. (15th March 2019) - Shi, Lingfeng; Shu, Gequn; Tian, Hua; Chen, Tianyu; Liu, Peng; Li, Ligeng
Abstract: For engine waste heat recovery, CO2 -based Transcritical Rankine Cycle (CTRC) system with preheating process has a strong capability of combining exhaust gas and engine coolant, thereby leading to improvement of output, efficiency improvement and the reduction in cooling load reduction. In previous researches, all the benefits were achieved and investigated mainly under ideal and stable engine conditions in previous researches. But in this study, various engine conditions were considered for a preheated CTRC test bench, namely starting and 'warm up' condition, stopping and idling condition, restarting condition and random condition. After system parameters (e.g. pressure, temperature) were measured, heat absorption quantity was calculated, and meanwhile net power output and thermal efficiency were estimated. The results show that the preheating process can improve the dynamic performance of the CTRC at various engine conditions. Firstly, the preheating process is beneficial for continuous output capacity and safe operation of CTRC. Besides, the preheating process also can avoid the sudden rise in the expansion inlet pressure under the stopping condition of engine, and meanwhile it plays an important energy supplement role in the random conditions of the engine, resulting in the cross change in the waste heat absorption from engine coolant and exhaust gas. Highlights: Preheating can improve dynamic performance of CTRC at various engine conditions. Preheating is beneficial for continuous output capacity and safe operation of CTRC. Preheating can avoid the sudden rise in pressure when engine stops. Preheating plays an important energy supplement role when engine restarts.